In vivo effect of three fractions of Larrea divaricata Cav. (jarilla) on the innate immune system: macrophage response against Candida albicans - Martino, Renzo Fabricio (2011)
Larrea divaricata Cav. (jarilla) is a plant with well-documented applications in folk medicine in Argentina. In this study, we aimed to evaluate functional parameters of peritoneal macrophages isolated from mice injected with three fractions (F1, F2 and F3) of L. divaricata. The response of macrophages against Candida albicans was evaluated. Cell viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test, apoptosis was evaluated using Giemsa, acridine orange/ethidium bromide and ladder assay, oxidative burst was assayed using nitroblue tetrazolium test and nitrite production using Griess assay. Cell stimulation and their ability to kill C. albicans in vitro were measured. The number and cell viability were similar to controls. However, we found that F1 induces pre-activation of macrophages, and this pre-activation is enhanced by C. albicans. The effects exerted by F1 make it more important than F2 and F3 for the treatment of disseminated candidiasis in patients with immunodeficiency diseases such as AIDS and chronic granulomatous disease, among others.